Greeks in Michigan - Frangos, Stavros (Book collections on Project MUSE., 2004)
The influence of Greek culture on Michigan began long before the first Greeks arrived. The American settlers of the Old Northwest Territory had definite notions of Greeks and Greek culture. America and its developing society and culture were to be the ""New Athens, "" a locale where the resurgence in the values and ideals of classical Greece were to be reborn. Stavros K. Frangos describes how such preconceptions and the competing desires to retain heritage and to assimilate have shaped the Greek experience in Michigan. From the padrone system to the church communities, Greek institut.